Evidence from ITIR-FCS Diffusion Studies that the Amyloid-Beta (Aβ) Peptide Does Not Perturb Plasma Membrane Fluidity in Neuronal Cells. Issue 18 (14th September 2018) - Ng, Justin; Kamm, Roger D.; Wohland, Thorsten; Kraut, Rachel S.
Abstract: The amyloid-beta (Aβ) peptide, commonly found in elevated levels in the brains of patients with Alzheimer's disease (AD) and in the cerebrospinal fluid of individuals presenting mild cognitive impairment, is thought to be one of the major factors resulting in the onset of AD. Although observed and studied at the molecular level for several decades, the exact disease pathology of AD is still not totally clear. One way in which Aβ is thought to affect neurons is by influencing cell membrane fluidity, which could result in abnormal synaptic or signaling function. The effects of Aβ on the fluidity of biological membranes have been studied using numerous membrane models such as artificial lipid bilayers and vesicles, living cells and membranes extracted from animal models of AD, yet there is still no consensus as to what effects Aβ has, if any, on membrane fluidity. As one of the most precise and accurate means of assaying membrane dynamics, we have thus chosen fluorescence correlation spectroscopy to investigate the issue, using fluorescent membrane-targeted probes on living cells treated with Aβ(1–42) oligomers and observing possible changes in membrane diffusion. Effects of Aβ on viability in different cell types varied from no detectable effect to extensive cell death by 72 h post-exposure. However, there was no change in the fluidity of either ordered membrane domains or the bulk membrane in any of these cells within this period. Our conclusion from these results is that perturbation of membrane fluidity is not likely to be a factor in acute Aβ-induced cytotoxicity. Graphical abstract: Unlabelled Image Highlights: For many years, researchers have been interested to know how amyloid-beta affects cell membrane fluidity due to the implications for the pathogenesis of Alzheimer's disease. However, more than 20 years of research has turned up conflicting and inconclusive results, due in part to shortcomings of the methods used to-date. In this study, we used a minimally invasive spectroscopy technique to measure the fluidity of fluorescent membrane probes in living cells. Apart from staining of the membrane using said probes, no further treatment or modification was done to the cell membrane. We found that despite being exposed to amounts of amyloid-beta peptide sufficient to trigger caspase activation and programmed cell death (apoptosis), fluidity of both disordered and ordered phase of the plasma membrane did not change in two neuroblastoma (SH-SY5Y and Neuro-2a) and one glioma (U87) cell line, of which the SH-SY5Y cell line was additionally neuronally differentiated. Our results indicate that acute amyloid-beta toxicity does not cause perturbations in the cell's plasma membrane fluidity and, by implication, membrane organization. Further investigation will be required to determine whether chronic, sub-cytotoxic amounts of amyloid-beta will cause any change in membrane fluidity.